Reduced grey matter perfusion without volume loss in early relapsing-remitting multiple sclerosis. Issue 5 (13th September 2013) - Debernard, Laëtitia; Melzer, Tracy R; Van Stockum, Saskia; Graham, Charlotte; Wheeler-Kingshott, Claudia AM; Dalrymple-Alford, John C; Miller, David H; Mason, Deborah F
Abstract : Background: Grey matter (GM) pathology in multiple sclerosis (MS) is associated with progressive long-term disability. Detection of GM abnormalities in early MS may therefore be valuable in understanding and predicting the long-term course. However, structural MRI measures such as volume loss have shown only modest abnormalities in early relapsing-remitting MS (RRMS). We therefore investigated for evidence of abnormality in GM perfusion, consistent with metabolic dysfunction, in early RRMS. Methods: 25 RRMS patients with ≤5 years disease duration and 25 age-matched healthy controls underwent 3 Tesla MRI with a pseudo-continuous arterial spin labelling sequence to quantify GM perfusion and a volumetric T1-weighted sequence to measure GM volume. Neurological status was assessed in patients and neuropsychological evaluation undertaken in all subjects. Voxel-based analysis was used to compare regional GM perfusion and volume measures in patients and controls. Results: There was reduced global GM perfusion in patients versus controls (50.6±5.8 mL/100 g/min vs 54.4±7.6 mL/100 g/min, p=0.04). Voxel-based analysis revealed extensive regions of decreased cortical and deep GM perfusion in MS subjects. Reduced perfusion was associated with impaired memory scores. There was no reduction in global or regional analysis of GM volume in patients versus controls. Conclusions: The decrease in GM perfusion in the absence of volume loss is consistent with neuronal metabolic dysfunction in early RRMS. Future studies in larger cohorts and longitudinal follow-up are needed to investigate the functional and prognostic significance of the early GM perfusion deficits observed.